Dedicated farnesyl diphosphate synthases circumvent isoprenoid‐derived growth‐defense tradeoffs in Zea mays. (31st August 2022) - Tang, Hoang V.; Berryman, David L.; Mendoza, Jorrel; Yactayo‐Chang, Jessica P.; Li, Qin‐Bao; Christensen, Shawn A.; Hunter, Charles T.; Best, Norman; Soubeyrand, Eric; Akhtar, Tariq A.; Basset, Gilles J.; Block, Anna K.
SUMMARY: Zea mays (maize) makes phytoalexins such as sesquiterpenoid zealexins, to combat invading pathogens. Zealexins are produced from farnesyl diphosphate in microgram per gram fresh weight quantities. As farnesyl diphosphate is also a precursor for many compounds essential for plant growth, the question arises as to how Z. mays produces high levels of zealexins without negatively affecting vital plant systems. To examine if specific pools of farnesyl diphosphate are made for zealexin synthesis we made CRISPR/Cas9 knockouts of each of the three farnesyl diphosphate synthases (FPS) in Z. mays and examined the resultant impacts on different farnesyl diphosphate‐derived metabolites. We found that FPS3 (GRMZM2G098569) produced most of the farnesyl diphosphate for zealexins, while FPS1 (GRMZM2G168681) made most of the farnesyl diphosphate for the vital respiratory co‐factor ubiquinone. Indeed, fps1 mutants had strong developmental phenotypes such as reduced stature and development of chlorosis. The replication and evolution of the fps gene family in Z. mays enabled it to produce dedicated FPSs for developmentally related ubiquinone production (FPS1) or defense‐related zealexin production (FPS3). This partitioning of farnesyl diphosphate production between growth and defense could contribute to the ability of Z. mays to produce high levels of phytoalexins without negatively impacting its growth. Significance Statement: A major goal for agricultural research is to develop crops that have both good yield and pest resistance. Often improving one of these traits has negative impact on the other, the so‐called growth‐defense tradeoff. In this study we uncover a mechanism in maize that allows the production of high levels of defense compounds using dedicated enzymes for shared precursor production. These findings can be used to guide synthetic biology approaches for agricultural improvement.